PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN BAHASA INGGRIS DI SDN 02 TIUMANG - Estuhono; Retno Pebrianti; Zumrotun Lutfiah (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
ABSTRACT This study aims to determine the effect of using the Talking Stick cooperative learning model on third-grade English. This is due to the low learning outcomes in English. This quantitative study employed an experimental method with a pre-experimental design. The research design used was a One Group Pretest-Posttest Design. This design only uses one experimental group. The study was conducted at SDN 02 Tiumang, Tiumang District, Dharmasraya Regency. The sample consisted of 23 students, all third-grade students. The data collection instrument used was a 20-item multiple-choice test, which had been tested for validity and reliability. The results showed that the average pretest score was 60.43, while the average posttest score was 84.13. The average score obtained was a difference of -23.7. This difference indicates an increase in the score compared to the average pretest score, indicating that students experienced improved learning outcomes after being treated with the Talking Stick learning model. The description of the research data from the pretest-posttest data analysis in hypothesis testing, using the Paired Sample T-Test, shows that the Sig. (2-tailed) value is 0.000, which means it is less than 0.05 or 0.000 <0.05. Therefore, Ha is accepted while H0 is rejected. Therefore, it can be said that there is a significant influence between the Talking Stick Cooperative Learning Model and English learning in grade III of SDN 02 Tiumang.